2011
DOI: 10.1080/13607863.2010.536133
|View full text |Cite
|
Sign up to set email alerts
|

Impaired digit span can predict further cognitive decline in older people with subjective memory complaint: A preliminary result

Abstract: Subjective memory complaint (SMC) is common among elderly people, and is thought to be part of mild cognitive impairment (MCI). We evaluated whether impaired digit span (IDS) in older people with SMC can predict wider impairment in future neuropsychological tests that correspond to MCI. After a mean of 6.6 years from the initial assessment, we reevaluated 16 subjects with SMC and normal digit span (NDS) scores (mean age 57.6 ± 8.1 years) and 28 subjects with SMC and IDS scores (mean age 59.7 ± 9.9 years). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…For example, a study that evaluated non-demented individuals with subjective memory complaints found that those with normal digit span scores (defined using age- and education-adjusted neuropsychological test scores) at baseline did not exhibit significant declines on verbal memory, visual memory, or executive function after a mean follow-up of 6.6 years, but had significant declines on the sum score of digit span forward and backward [62]. On the other hand, age-, sex-, and education-matched individuals with impaired digit span scores at baseline had significant declines on tests of verbal learning and animal fluency but not on any other cognitive test.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study that evaluated non-demented individuals with subjective memory complaints found that those with normal digit span scores (defined using age- and education-adjusted neuropsychological test scores) at baseline did not exhibit significant declines on verbal memory, visual memory, or executive function after a mean follow-up of 6.6 years, but had significant declines on the sum score of digit span forward and backward [62]. On the other hand, age-, sex-, and education-matched individuals with impaired digit span scores at baseline had significant declines on tests of verbal learning and animal fluency but not on any other cognitive test.…”
Section: Discussionmentioning
confidence: 99%
“…Working memory and visuospatial ability have been proposed as functions that decline slowly in MCI patients [63]. A recent study showed that subjects presenting subjective cognitive complaints and impairment in DS might have a higher risk of future conversion to MCI but did not compare the DS predictive value to other memory tests [38]. …”
Section: Discussionmentioning
confidence: 99%
“…The Digit Span (DS) test measures auditory attention, immediate span of learning, and working memory. Impairment in the DS test was associated with future cognitive decline [38, 39]. However, it appears that working memory does not decline early in the neurodegenerative process of AD [40].…”
Section: Introductionmentioning
confidence: 99%
“…Visual memory tests that have received attention in the literature include Wechsler Memory Scale’s Visual Reproduction [15] and the Rey–Osterrieth Complex Figure Test (RCFT) [2325]. Measures of executive and language functioning that may predict conversion include Trail Making Test B (TMT B) [15,2529], Wechsler Adult Intelligence Test-Revised digit symbol coding [21], Stroop Color Naming [30], Wechsler Memory Scale-Revised digit span [31], semantic fluency [32,33] and the Boston Naming Test (BNT) [34,35]. …”
mentioning
confidence: 99%